2002
DOI: 10.1354/vp.39-5-572
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Hyperplasia, Polyps, and Adenomyosis Associated with Unopposed Estrogen in Rhesus Monkeys (Macaca mulatta)

Abstract: Abstract. The purpose of this study was to evaluate the effects of estrogen and progesterone on the vaginal mucosa and their role in vaginal transmission of simian immunodeficiency virus. Incidentally, endometrial hyperplasia was observed in estrogen-treated monkeys at necropsy. Six adult female rhesus monkeys (Macaca mulatta) were ovariectomized and 120 days later received two subcutaneous implants, each containing 200 mg estradiol. The animals were sacrificed 17-27 months later and the uterus examined at nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 20 publications
4
38
0
1
Order By: Relevance
“…However aberrant aromatase expression has been previously detected in the eutopic endometrium of patients with endometriosis, adenomyosis and endometrial polyps [8,9,11]. This may suggest a common etiology in these conditions, involving chronic local exposure to estrogens that will lead to the development of these pathologies, thus corroborating previous studies carried out in rhesus monkeys [22].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However aberrant aromatase expression has been previously detected in the eutopic endometrium of patients with endometriosis, adenomyosis and endometrial polyps [8,9,11]. This may suggest a common etiology in these conditions, involving chronic local exposure to estrogens that will lead to the development of these pathologies, thus corroborating previous studies carried out in rhesus monkeys [22].…”
Section: Discussionsupporting
confidence: 79%
“…It would be an oversimplification to consider local estrogen production to be the only stimulus of myoma development, since other factors may act synergistically in association with aromatase expression, including cytogenetic abnormalities that might affect growth rates [3,5]. Experimental studies carried out in primates have shown that chronic exposure of the uterus to estrogens leads to the development of myomas, endometrial polyps, hyperplasia and adenomyosis [22]. Although these findings suggest that excessive estrogenic stimulation may be an important factor in the genesis of various uterine pathologies, thus explaining their common association, genetic and other factors probably play important roles in determining which pathology will develop in response to excessive estrogenic stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged progesterone treatment following diethylstilboestrol also induced adenomyosis in ovariectomized mice, suggesting a link between progesterone and the development of adenomyosis (Ostrander et al 1985). On the other hand, estrogen unopposed by progestogen administered to ovariectomized rhesus monkeys induced adenomyosis (Baskin et al 2002).…”
Section: Introductionmentioning
confidence: 96%
“…These estrogen levels are within the physiological range [43][44][45] , even though exposure was continuous and unopposed by progesterone. Histology of endometrial tissue taken by the vaginal route, hysterotomy or hysterectomy showed proliferation of glands and stroma ( fig.…”
Section: Estrogen Treatmentmentioning
confidence: 91%
“…1 ). In previous studies on rhesus monkeys, subcutaneous estradiol implants were found to successfully induce continuous serum estradiol levels within the physiological range [41,42] and an endometrium with proliferative histological characteristics [43] . Thus, our 3 female rhesus monkeys received one-third of a Meno-Implant (estradiol, 20 mg; Organon, Oss, The Netherlands) placed subcutaneously in the abdominal area.…”
Section: Estrogen Treatmentmentioning
confidence: 99%